Screening of novel therapeutic targets and chimeric vaccine construction against antibiotic-resistant Yersinia Enterocolitica - Shah, Mohibullah; Fatima, Rouman; Sarfraz, Asifa; Khan, Muhammad Umer; Ejaz, Hasan; Alam, Maqsood; Aziz, Shahid; Nishan, Umar; Ali, Abid; Bari, Ahmed; Ojha, Suvash Chandra (Frontiers in Immunology, 2025)
Yersinia enterocolitica is known to cause a variety of infections, including mild gastroenteritis and severe systemic disease. This bacterium has developed resistance to several antibiotics, including cephalosporins, penicillins, and fluoroquinolones. Despite significant advances in vaccine formulation against Y. enterocolitica, there is no FDA-licensed vaccine available against it. Herein, the subtractive proteomics approach was utilized to determine the potential drug and vaccine targets, and then reverse vaccinology was utilized to formulate effective vaccines against this pathogen. A core proteome was constructed from the available 22 complete genomes of Y. enterocolitica. Screening resulted in 14 non-human homologous, essential, and virulent proteins being identified as drug targets, while 15 were identified as vaccine targets. The predicted vaccine targets were analyzed, and as a result, two proteins met the criteria for epitope prediction. The epitopes were subjected to a screening pipeline to identify epitopes capable of inducing both T- and B-cell-mediated immune responses. Four vaccine constructs were designed using the selected epitopes by adding the appropriate adjuvants and linkers. The chosen T-cell epitopes showed the possibility of covering 99.26% of the global population. The constructs V1, V2, V3, and V4 were top-ranked based on their physicochemical properties and selected for further analysis. These four vaccines were computationally docked with immune receptors TLR4 and TLR5 to evaluate binding affinities, with V2 and V4 displaying the highest binding affinities with TLR4. The MD simulations, NMA, binding free energy, PCA, and DCCM analysis ensured the stability of complexes. Immune simulations predicted a high immunological profile for the V2 and V4 constructs. Furthermore, in-silico cloning assured that the proposed vaccines could be efficiently expressed in the E. coli (K12) vector. This study provides valuable insights into developing effective vaccines against Y. enterocolitica; however, the immunogenicity of the designed vaccine requires experimental validation.